Naselja in prihodnost - Zupančič, Domen (Urbani izziv, 2002)
Current ongoing societal processes allow me to say that all humanity must foresee the great opportunity to change direction from market driven development to human scale sustainable development as the only way to achieve whole scale growth. In the achievement of this transition the most important observation is that it could be achieved without miraculous technologies or drastic transformations of human societies. The main requirement is the translation of basic knowledge to the people, especially in less developed countries and to the younger generations. Without sincere political will our common future cannot be reached. In my essay I tried to demonstrate what may happen in the future, if the no-dialogue community develops. Sustainable development is the only correct route if we want to get where we are going - the future well being of all human kind.
Keywords: družbeni razvoj; enakost; naselja; prostorsko planiranje; sonaravni razvoj; spatial planning; sustainable development; trajnostni razvoj